Pola aktivitas enzim ligninolitik Pleurotus ostreatus pada limbah sludge pabrik kertas Activity pattern of ligninolytic enzyme of Pleurotus ostreatus in sludge waste of paper factory - Happy WIDIASTUTI; . TRI-PANJI (Menara Perkebunan, 2008)
Summary Sludge is a solid waste abundantly available on paper factory that is economically unutilized and tends to pollute environment. This waste can be used as growth media for oyster mushroom (Pleurotus ostreatus) as edible mushroom and ligninolytic enzymes production as well. A research has been conducted to study the activity pattern of ligninolytic enzymes of oyster mushroom grown on the sludge waste of recycle paper factory. Six treatments were examinated consisted of three media combinations (sawdust, sludge, sludge mixed with sawdust), with and without supplementing with rice bran, lime, and gypsum, and two mushroom strains Bogor oyster mushroom (JTB) and China Taipei oyster mushroom (JTT). Monitoring of ligninolytic enzyme activity consisting of laccase, mangan peroxidase (Mn-P) and lignin peroxidase (Li-P),  was subsequently regularly started since inoculation, at vegetative phase (four and six weeks), primordial formation, phase of fruiting body formation, and two weeks after formation of fruiting body. Each treatment was repeated three times, so that 216 bag logs of oyster mushroom cultures were performed. The results showed that laccase, Mn-P, and Li-P activities could be observed on sludge or mixture of sludge+sawdust media inoculated with P. ostreatus. Generally, the highest activity of ligninolytic enzymes especially for laccase and MnP were observed at the first vegetative growth phase i.e. before emerging primordial of fruiting body (1.697 & 2.113 U/mL, 4.394 & 2.314 U/mL  respectively for JTB and JTT laccase and JTB & JTT Mn-P). The highest Li-P activity was affected by the kind of media and strain of inoculum. In sludge medium, the highest Li-P activity was observed in  vegetative growth phase (2.706 & 4.014 U/mL respectively for JTB and JTT) while in a mixture of sludge + sawdust the highest activity of that enzyme was observed in primordial phase of growth (2.509 & 1.9 U/mL respectively for JTB and JTT). Addition of supplement to the sludge increased ligninolytic activity, while laccase activity of sludge was suggested could be more enhanced by mixing the sludge with sawdust and enrich with rice bran, gypsum and lime. Ringkasan                                                Sludge merupakan limbah padat yang tersedia melimpah di pabrik kertas dan belum dimanfaatkan secara ekonomis sehingga berpotensi mencemari lingkungan. Limbah ini dapat dimanfaatkan sebagai medium tumbuh jamur konsumsi seperti jamur tiram (Pleurotus ostreatus) dan penghasil enzim ligninolitik. Penelitian dilakukan untuk mempelajari pola aktivitas enzim ligninolitik jamur tiram pada limbah sludge pabrik kertas selama fase vegetatif sampai setelah fase generatif. Enam perlakuan yang diuji berupa tiga kombinasi komposisi medium (serbuk gergaji, sludge, campuran sludge dan serbuk gergaji), dengan dan tanpa pengayaan, yaitu penambahan dedak, kapur, dan gipsum,  serta dua strain jamur tiram Bogor (JTB) dan jamur tiram China Taipei (JTT). Pengamatan aktivitas enzim ligninolitik meliputi lakase, mangan peroksidase (Mn-P) dan lignin peroksidase  (Li-P) dilakukan sejak saat inokulasi, pada fase vegetatif (empat dan enam minggu), pada saat pembentukan primordia, fase tubuh buah, dan dua minggu setelah pembentukan tubuh buah. Masing-masing perlakuan diulang tiga kali sehingga terdapat 216 bag log jamur tiram. Hasil penelitian menunjukkan bahwa aktivitas ligninolitik dijumpai pada medium sludge dan campuran sludge+serbuk gergaji yang diino-kulasi P. ostreatus. Aktivitas enzim ligninolitik tertinggi khususnya lakase dan MnP teramati pada fase pertumbuhan vegetatif pertama yaitu sebelum terbentuknya primordia (1,697 & 2,113 U/mL, 4,394 & 2,314 U/mL  masing-masing untuk lakase JTB dan JTT dan MnP  JTB & JTT). Aktivitas LiP tertinggi dipengaruhi oleh jenis medium dan strain inokulum. Pada medium sludge, aktivitas LiP tertinggi dijumpai pada fase vegetatif (2,706 & 4,014 U/ml masing-masing untuk JTB dan JTT) sedangkan pada medium campuran sludge+serbuk gergaji, aktivitas enzim  ter-tinggi dijumpai  pada fase primordia (2,509 & 1,9 U/ml berturut-turut untuk JTB dan JTT). Pengayaan sludge meningkatkan aktivitas ligninolitik, sedangkan aktivitas lakase pada sludge diduga dapat lebih ditingkatkan dengan menambahkan serbuk gergaji disertai pengayaan berupa gipsum, dedak, dan kapur.